2019
DOI: 10.18203/2394-6040.ijcmph20190612
|View full text |Cite
|
Sign up to set email alerts
|

A hospital-based cross-sectional study on yoga and meditation in patients of hypertension in Western India

Abstract: Background: Yoga and meditation hold promise as a non-pharmacological management of hypertension as they have shown to lower blood pressure. This study aimed at (1) assessing the awareness about benefits of yoga and meditation in hypertension among patients and finding its socio-demographic correlates, (2) estimating the practice of yoga and meditation in hypertensives, its pattern and impact on blood pressure control.Methods: This cross-sectional study was conducted on 400 hypertensive patients. Statistical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
1
2
0
Order By: Relevance
“…This study individuals aged 30-59 years, a demographic typically associated with peak economic productivity. Intriguingly, the prevalence of hypertension was lowest among the younger age groups, a trend in line with findings from studies conducted in Jamnagar city [18] . The majority of patients were female, a consistent pattern observed across diverse regions such as Turkey, India, the USA, and Nigeria, aligning with previous research [19,22] .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This study individuals aged 30-59 years, a demographic typically associated with peak economic productivity. Intriguingly, the prevalence of hypertension was lowest among the younger age groups, a trend in line with findings from studies conducted in Jamnagar city [18] . The majority of patients were female, a consistent pattern observed across diverse regions such as Turkey, India, the USA, and Nigeria, aligning with previous research [19,22] .…”
Section: Discussionsupporting
confidence: 89%
“…In our study, we found that patients who practiced yoga and/or meditation demonstrated lower systolic blood pressure (SBP) and diastolic blood pressure (DBP) compared to non-practicing patients, with reductions of 8.7 mmHg and 6.4 mmHg, respectively, which proved to be statistically significant. Similarly, a study conducted in Gujarat reported a significant decrease in SBP, although the reduction in DBP was not statistically significant [18] . In a randomized controlled trial by Saptharishi L et al, the intervention of yoga alone resulted in a reduction of 2 mmHg in systolic blood pressure (SBP) and 2.9 mmHg in diastolic blood pressure (DBP) [24] .…”
Section: Discussionmentioning
confidence: 89%
“…31 A hospital-based cross-sectional study on yoga and meditation in patients of hypertension in western India also reported poor practice (12.8%). 32 Another study reported about one-fifth (19.8%) of patients with epilepsy were practising yoga. 17 As per a recent nationwide survey, only 11.8% of the respondents practised yoga, hence there exists a similar knowledge practice gap throughout the country.…”
Section: Discussionmentioning
confidence: 99%